Mutations and Variants Analysis of Inhibin Gene Subunits in Women with Premature Ovarian Failure - Juman Khaleel Al-Sabbagh; Mohammad Sabri A. Razzaq; Milal M. Abd-Al-Rudha (University of Thi-Qar Journal of Science, 2020)
This study aimed to illustrate the role of inhibin gene as a candidate gene in women with premature ovarian failure (POF) . In this studysixty women who suffered from POF ; and have menopause at least 8 months after the last period , whose ages range between (20-39) years, venous blood samples were collected from these patients who are admitting to the Children and Maternity Hospital and Al-Hilla teaching hospital in Hilla city/Iraq . Also, forty women with no history of menopause with age range approximately matched to that of patients were included as control group . The genotyping was carried out by using PCR , RFLP and SCCP techniques to identify variants in some of candidates genes associated with POF . So regarding to INHα1 gene , the result showed that there is a significant differences between patients and control groups that related to the presence this subunit .The result of RFLP to investigate the variant in this gene showed that most of patients and all control were homozygous for the wild type G allele , and G allele frequency was (92.8%) in patients group and (100%) in control group whereas A allele frequency was (7.2%) POF patients group and (0%) in the control group . The GG genotypes have frequency (85.7%) in POF and (100%) in control group, whereas the AG was found to be (14.3%) and (0%) in patients and control respectively . The results of INHβA1, INHβB1and INHβB2 mutational screening , it was found that there is a significant differences between presence and absence of this gene in patients and control group at (P value 0.01) for INHβA1. , while no one of patients and control groups show missing of INHβB1and INHβB2 subunits . Using SSCP technique to investigate the presence of variants in INHβA1, INHβB1and INHβB2 genes . The results illustrate that there is a significant differences in comformational changes of these gene subunits in patients and control subjected to this study. And this gave an indicator to relationship of the variants in these subunits with arising of POF in women in our population .